Negosiasi Identitas Budaya: Resistensi dan Hibriditas Mahasiswa di Tengah Dominasi Budaya Populer Global - Nurcholis Sunuyeko; Ike Dian Puspita Sari (Universitas Insan Budi Utomo, 2025)
This research analyzes cultural identity negotiation strategies among university students in Indonesia amidst the dominance of global popular culture, specifically the influence of Hallyu and Westernization. Employing a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews and digital observations of 12 students in urban environments. The results indicate that students do not passively adopt foreign cultures; instead, they undergo a